Searching for optimal experimental designs using space-filling curves - Skubalska-Rafajłowicz, Ewa; Rafajłowicz, Ewaryst (1953- ) (Zielona Góra: Uniwersytet Zielonogórski)
A new approach to the standard problem of searching for optimal experimental designs is considered. It consists in replacing a multidimensional search for global maxima by a one-dimensional global search. The points found in this way are then transformed to the multivariate design domain by using a space-filling curve.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka